The contribution of FTO and UCP-1 SNPs to extreme obesity, diabetes and cardiovascular risk in Brazilian individuals - Ramos Adauto V; Bastos-Rodrigues Luciana; Resende Bruna A; Friedman Eitan; Campanha-Versiani Luciana; Miranda Debora M; Sarquis Marta; De Marco Luiz (BMC, 2012)
Abstract Background Obesity has become a common human disorder associated with significant morbidity and mortality and adverse effects on quality of life. Sequence variants in two candidate genes, FTO and UCP-1, have been reported to be overrepresented in obese Caucasian population. The association of these genes polymorphisms with the obesity phenotype in a multiethnic group such as the Brazilian population has not been previously reported. Methods To assess the putative contribution of both FTO and UCP-1 to body mass index (BMI) and cardiovascular risk we genotyped SNPs rs9939609 (FTO) and rs6536991, rs22705565 and rs12502572 (UCP-1) from 126 morbidly obese subjects (BMI 42.9 ± 5.6 kg/m2, mean ± SE) and 113 normal-weight ethnically matched controls (BMI 22.6 ± 3.5 kg/m2, mean ± SE). Waist circumference, blood pressure, glucose and serum lipids were also measured. Each sample was also genotyped for 40 biallelic short insertion/deletion polymorphism (indels) for ethnic assignment and to estimate the proportion of European, African and Amerindian biogeographical ancestry in the Brazilian population. Results Cases did not differ from controls in the proportions of genomic ancestry. The FTO SNP rs9939609 and UCP-1 SNP rs6536991 were significantly associated with BMI (p= 0.04 and p<0.0001 respectively). An allele dose dependent tendency was observed for BMI for rs6536991 sample of controls. No other significant associations between any SNP and hypertension, hyperlipidemia and diabetes were noted after correction for BMI and no significant synergistic effect between FTO and UCP-1 SNPs with obesity were noted. There was not an association between rs9939609 (FTO) and rs6536991 (UCP-1) in with maximum weight loss after 1 year in 94 obese patients who underwent bariatric surgery. Conclusion Our data are consistent with FTO rs9939609 and UCP-1 rs6536991 common variants as contributors to obesity in the Brazilian population.